Construct and Criterion Validity of the Postmenopause Sexuality Questionnaire - PMSQ - Maria José Ferreira Lima; Marília Duarte Valim; Sebastião Freitas de Medeiros
Abstract Objective To assess the construct and criterion validity of the Postmenopause Sexuality Questionnaire (PMSQ). Methods The present methodological questionnaire validation study included postmenopausal women. The construct validity was tested by factor analysis and the criterion validity was performed using the correlation between the PMSQ and the Female Sexual Function Index (FSFI). The ROC curve was used to verify sensitivity, specificity and to determine the cutoff point of the PMSQ. Results A total of 181 women with amean age of 56.4 ± 5.7 years old were evaluated. The exploratory factor analysis showed that the PMSQ presented Kaiser test = 0.88 and χ2 = 3293.7 (p < 0.001), commonalities ≥ 0.5, and extraction of 9 factors with eigenvalue ≥ 1; explaining 66.3% of the total variance. The PMSQ presented factor loadings between 0.4 and 0.8. A strong correlation between the 2 questionnaires (r = 0.79; p = 0.000) was shown. The cutoff point of the PMSQ was ≤ 55.5, assuming 87.9% sensitivity and 78.9% specificity (p < 0.001). Conclusion Since the PMSQ showed a strong correlation with the FSFI questionnaire, it presented good psychometric properties to assess the sexuality in postmenopausal women. Based on these results, the PMSQ could be widely tested as a specific instrument to examine the sexual function in postmenopausal women. Future studies, designed to examine the PMSQ instrument in different populations, are needed.